Study of solar radiation effect on radio signal using plasma antenna - Umar, R.; Dagang, A.N.; Azmi, F.S. (2021)
Plasma antenna can be formed by energizing glass tubes which are filled with neutral gases. It works similarly as metal antenna where it can transmit and receive wireless signal. This study aims to investigate the effect of weather focused on solar radiation towards the performance of plasma antenna represented by signal strength. Fluorescent lamp was set as plasma because it used ionized gas as its conducting element instead of metal. Execution of electrical properties measurements need to be done first, in order to obtain discharge current and voltage values, that need to be used into Glomac programming for the generation of electron temperature and electron density. Next, calculations of the plasma properties was performed to derive the value of plasma and collision frequencies. The plasma properties are important parameters to design and simulate plasma antenna using Computer Simulation Technology (CST). Antenna parameters in terms of return loss, gain, directivity and radiation pattern can be simulated using CST. Signal strength experiment was conducted to evaluate plasma antenna performance in terms of its capability to capture the signals and analyse the effect of solar radiation on that particular moment through the rate of power level over time versus solar radiation data. It was observed at the highest solar radiation rate which is 920 V/m, the power level recorded is the lowest value at-172.93 dBm. Therefore, the signal strength received by the plasma antenna shows remarkable changes under the influence of solar radiation.